The distribution and risk of mercury in Shenzhen mangroves, representative urban mangroves affected by human activities in China. (February 2020) - Shi, Cong; Yu, Lingyun; Chai, Minwei; Niu, Zhiyuan; Li, Ruili
Abstract: Sediments were collected from urban mangroves in Shenzhen, China, including Shajing (SJ) and Xixiang (XX) featured with industrial district; Futian (FT) and Baguang (BG) featured with central business district and ecological preserve, respectively. Distributions, pollution levels and human health risks of Hg were explored. In both surface and vertical sediments, mean Hg concentration was highest in SJ mangrove, which may be due to its proximity to point-source discharge of Maozhou River in Pearl River Estuary, China. Sediment properties (pH, salinity, TOC and particle size) had limited impact on Hg accumulation due to their non-significant correlations. Geo-accumulation index, pollution load index, potential ecological risk index, and the ecological risk assessment code showed the highest ecological risk in SJ mangrove, followed by XX, FT, and BG mangroves. The assessment of human health risks showed that public experience little adverse health risk due to exposure to Hg polluted sediment in urban mangroves. Highlights: Hg levels in sediments of urban mangroves were Shajing > Xixiang > Futian > Baguang. Sediment properties had limited impact on Hg accumulation in mangrove sediments. The ecological risk of Hg was highest in Shajing, compared with other mangroves. There was no/low non-cancer risk in terms of exposure to Hg in mangrove sediments.